2012
DOI: 10.1177/0734904111429272
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of the effect of sample orientation on the pyrolysis and ignition of wood slabs exposed to radiation

Abstract: The effect of sample orientation (vertical and horizontal) on the pyrolysis and ignition of wood exposed to radiation has been studied with experimental and numerical methods in the present article. Experimental results show that the pyrolysis rate of vertically oriented wood exposed to radiation is higher than for horizontally oriented wood exposed to radiation. Pyrolysis gas significantly dominates the process of pyrolysis of wood exposed to radiation. Accounting for radiation absorption by pyrolysis gas, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Babrauskas 1 concluded that ignition times for the vertical orientation are longer than for the upward orientation. Similar results were also reported by Shields et al 2 However, an opposite result was obtained by Yang et al 3 He used the parallel silicon–carbide rods as radiation source, but found ignition times for vertical orientation are somewhat shorter. Shields et al 2 reported that the ignition times for the downward orientation are about three times longer than those for upward orientation by using the ISO 5657 apparatus.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Babrauskas 1 concluded that ignition times for the vertical orientation are longer than for the upward orientation. Similar results were also reported by Shields et al 2 However, an opposite result was obtained by Yang et al 3 He used the parallel silicon–carbide rods as radiation source, but found ignition times for vertical orientation are somewhat shorter. Shields et al 2 reported that the ignition times for the downward orientation are about three times longer than those for upward orientation by using the ISO 5657 apparatus.…”
Section: Introductionsupporting
confidence: 84%
“…Besides, the radiation blockage for the upward case is noticed to be greater than the vertical case. 3 This is because of the fact that for the vertical case, the pyrolysis gas flow upward along the surface, leading to smaller radiation attenuation than the upward case.…”
Section: Surface Temperaturementioning
confidence: 99%
“…Babrauskas [ 11 ], Shields [ 4 ] and Tsai [ 12 ] found the ignition time ratio of vertical and horizontal is 1.2/1.4. However, with the different location of pilot, Yang et al [ 13 ] found ignition times of wood for vertical orientation are shorter than horizontal, which is different from the result of Babrauskas and Shields. Tsai [ 12 ] conducted experimental work on the orientation effect to study the thermal processes in solid prior to ignition, while the pyrolysis process was ignored.…”
Section: Introductionmentioning
confidence: 94%
“…This was attributed to the differences in radiation attenuation in horizontal and vertical sample orientations owing to the difference in the structure of the pyrolysis gas plume and the fact that radiation absorption by pyrolysis gas was significantly different in the two configurations. Yang et al [120] reported that for horizontal samples, absorption of radiation by pyrolysis gas is stronger, and hence the net incident heat flux into the sample surface is less than for vertical samples. Thus, in the presence of a piloted ignition source, the ignition times of horizontal samples are slightly longer than the ones of vertical samples, despite the same distance between the sample and the radiant heater.…”
Section: Geometry / Configurationmentioning
confidence: 99%